Analisis Perubahan Garis Pantai Menggunakan SIG serta Dampaknya terhadap Kehidupan Masyarakat di Sekitar Muara Sungai Rejoso Kabupaten Pasuruan - Chatarina Muryani (Forum Geografi, 2010)
This research was conducted due to the rapid process of sedimentation around Rejoso estuary allegedly causes the land use and shorelines changes in the area. This research aims to ascertain (a) the changes in land use of research areas (years 1981-2009), (b) the changes of shorelines (year 2009-2010), and (c) the impacts of shorelines changes towards social life communities. Materials used in the research were aerial photographs in black and white panchromatic (year 1981; scale: 1:50.000), RBI Map of Rejoso Sheets (year 2000; scale: 1:25.000) and IKONOS image (year 2005 completed with field survey (year 2009). The steps of the research include (1) Cutting of aerial photographs, maps and images of the selected area, (2) radiometric and geometric correction, (3) digitization of shorelines and boundaries of land use, (4) field surveys to determine new boundaries which apply the GPS, (5) maps improvement based on the field survey, (6) maps overlay to analyze the changes in land use and in shorelines. Furthermore, the results of the research indicate (a) changes of land use (years 1981- 2009) including sea-fishpond (172.8 ha), sea-mangrove forest (67.0 ha), sea-bare land (coast) 51.4 ha, mangrove forest-fishpond (76.7 ha), fishpond-settlement (10.3 ha) , fishpond-rice field (7.2 ha), fishpond-mangrove forest (2.9 ha), rice field-fishpond (7.1 ha) and rice field-settlement (4.8), (b) changes in shorelines morphology, such as the changes in the estuary from concave to convex, shorelines advancing towards the sea approximately 1 km, the expansion of research area which is 141.9 ha and between years 1981 to 2000 approximately 133 ha, (c) the extension of the coastal area encouraging people to make new fishponds by converting the mangrove forests. Therefore, The Government of Pasuruan regency is recommended to strengthen the monitoring process towards spatial pattern of the coastal areas.